(NaRHITEKTURA ANTI^NYH SOORUVENIJ gARNI (B/s - d; (NtER(B-(NmINASQN(B, (Na(B.(Na(B.s ((NeREWAN (B:s (NsOWETAKAN GROH(B,s, 1988)
(NrEZ@ME(B: (NANGL(B.s
(NkOMMENT(B.: (NS(B. 185-210s
Keywords: (NaRHITEKTURAs -- (NaRMENIQs; (NaRHITEKTURA ANTI^NAQs -- (NgARNIs; (NiSTORIKO(B-(NARHITEKTURNYE PAMQTNIKI (B- (NaRMENIQs